Ocean community warming responses explained by thermal affinities and temperature gradients - Burrows, Michael T; Bates, Amanda E; Costello, Mark J; Edwards, Martin; Edgar, Graham J; Fox, Clive J; Halpern, Benjamin S; Hiddink, Jan G; Pinsky, Malin L; Batt, Ryan D; Molinos, Jorge Garcia; Payne, Benjamin L; et al. (Nature Climate Change, 2019)
As ocean temperatures rise, species distributions are tracking towards historically cooler regions in line with their thermal affinity1,2. However, different responses of species to warming and changed species interactions make predicting biodiversity redistribution and relative abundance a challenge3,4. Here, we use three decades of fish and plankton survey data to assess how warming changes the relative dominance of warm-affinity and cold-affinity species5,6. Regions with stable temperatures (for example, the Northeast Pacific and Gulf of Mexico) show little change in dominance structure, while areas with warming (for example, the North Atlantic) see strong shifts towards warm-water species dominance. Importantly, communities whose species pools had diverse thermal affinities and a narrower range of thermal tolerance showed greater sensitivity, as anticipated from simulations. The composition of fish communities changed less than expected in regions with strong temperature depth gradients. There, species track temperatures by moving deeper2,7, rather than horizontally, analogous to elevation shifts in land plants8. Temperature thus emerges as a fundamental driver for change in marine systems, with predictable restructuring of communities in the most rapidly warming areas using metrics based on species thermal affinities. The ready and predictable dominance shifts suggest a strong prognosis of resilience to climate change for these communities.